Submarine landslides on the Black Sea shelf near Abrau Peninsula and their relation to seismicity; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 337, № 2 - Roslyakov A. G. Alexandr Gennadievich; Ananyev R. A. Roman Alexandrovich; Krylov A. A. Artem Alexandrovich; Kovachev S. A. Sergey Anatolyevich; Dmitrevsky N. N. Nikolai Nikolaevich; Marinova Y. G. Yulia Gennadievna; Bykhalova O. N. Olga Nikolaevna; Lobkovsky L. I. Leopold Isaevich; Semiletov I. P. Igor Petrovich (2026, 2026)
Relevance. The Abrau Peninsula is a unique natural area that has attracted the interest of scientists from a wide range of research fields. Its main feature is the giant landslide structures that have no analogs in other areas of the Caucasian coast of the Black Sea. These structures are expressed not only in modern land relief and coastline outlines but also in the morphology of the seabed of the adjacent part of the shelf. The mechanism of the formation of such large-scale deformations and the driving forces that initiate these processes remain debatable. The conducted research will allow us to resolve important questions about the mechanisms of formation and age of landslides, the stages of their development, and the possibility of further activation of landslide processes, including in the near future. Aim. To process and interpret hydroacoustic and seismic data from the Black Sea shelf near the Abrau Peninsula; identify the relationship between gravity-driven zones and seismicity in the study area. Methods. This work is based on geophysical survey data conducted by the authors in 2011, 2020, and 2025. Seabed mapping was conducted using Kongsberg Simrad EM3002D and WASSP WMB-3250 multibeam echosounders. Seismic surveys were carried out in low- and high-frequency modes using an SES-2000 parametric profiler and a single-channel complex with a boomer seismic source. Results and conclusions. In the area of the Black Sea shelf adjacent to the Abrau Peninsula, seismic and bathymetric data have revealed acoustically transparent units and local seabed uplifts that complicate the bottom topography. These features are located on the underwater continuation of seismo-gravitational land structures. Seismic events in the late Holocene played a key role in the formation of these structural features. Dynamic impacts from earthquakes with magnitudes typical for the region can generate dynamic impacts strong enough to liquefy watersaturated marine sediments. This process can trigger landslides and facilitate the ascent of fluids from the seabed, leading to the formation of cone-shaped uplifts